Radiological protection in the perspective of health professionals exposed to radiation - Vinícius Martins Dias Batista; Monica Oliveira Bernardo; Flávio Morgado; Fernando Antonio de Almeida
ABSTRACT Objective: To evaluate the knowledge of health professionals about radiological protection and to implement educational actions to promote a safe working environment for professionals, patients and companions. Method: An exploratory cross-sectional study, applying a questionnaire to 59 participants from different sectors of a teaching hospital. Open-ended questions were analyzed through the discourse of the collective subject and closed-ended questions were analyzed through quantitative analysis. Results: In the opinion of the participants, their professional training did not offer radioprotection class or the training was insufficient for the practice. In addition, the work environment does not provide regulatory norms and training on radioprotection. Most participants do not have solid knowledge and do not present safe behavior in radioprotection. In the internal week for the prevention of work accidents, a lecture and a theatricalisation about the topic of radioprotection were conducted and a booklet was distributed. Conclusion: Radiation protection education is necessary in the curricula of the training courses for health professionals and in the work environment.